#### Answer

1

#### Work Step by Step

Multiply the base by itself the number of times that the exponent indicates.
(-1)$^6$ = (-1)(-1)(-1)(-1)(-1)(-1) = (1)(-1)(-1)(-1)(-1) = (-1)(-1)(-1)(-1) = (1)(-1)(-1) = (-1)(-1) = 1

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.